2009
DOI: 10.2165/11316580-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Adverse Effect Reporting in Placebo Groups in SSRI and Tricyclic Antidepressant Trials

Abstract: Adverse effect profiles reported in clinical trials are strongly influenced by expectations from investigators and patients. This difference cannot be attributed to ascertainment methods. Adverse effect patterns of the drug group are closely related to adverse effects of the placebo group. These results question the validity of the assumption that adverse effects in placebo groups reflect the 'drug-unspecific effects'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
147
1
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 165 publications
9
147
1
12
Order By: Relevance
“…Some lessons could also be learned from pharmacological research, although the reporting of safety data has been found unsatisfactory in pharmacological trials as well [11,13,56,57]. Most adverse events are detected and recorded only if they occur early during pharmacological treatment, or if they were anticipated at the phase of trial planning [58].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Some lessons could also be learned from pharmacological research, although the reporting of safety data has been found unsatisfactory in pharmacological trials as well [11,13,56,57]. Most adverse events are detected and recorded only if they occur early during pharmacological treatment, or if they were anticipated at the phase of trial planning [58].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Most adverse events are detected and recorded only if they occur early during pharmacological treatment, or if they were anticipated at the phase of trial planning [58]. A recent systematic review of the reporting of adverse effects in RCTs of antidepressants for anxiety and depressive disorders found that structured assessment methods (e.g., checklists or self-rating scales) yielded considerably higher rates of reported symptoms as compared to unstructured assessment methods [57]. However, certain unstructured approaches, such as open-ended questions, can be crucial in evoking patient reports of rare but serious adverse events.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…There is recent evidence that side-effect patterns of the drug group strongly influence those in the placebo group in anti-migraine trials [48]. A systematic review by our group investigated adverse effect patterns in antidepressant trials [49]. Randomized controlled trials that tested SSRIs (122 trials) and TCAs (21 trials) in the treatment of depressive disorders and anxiety disorders were included (for further details see [49]).…”
Section: Nocebo Effects In Antidepressant Trialsmentioning
confidence: 99%
“…A systematic review by our group investigated adverse effect patterns in antidepressant trials [49]. Randomized controlled trials that tested SSRIs (122 trials) and TCAs (21 trials) in the treatment of depressive disorders and anxiety disorders were included (for further details see [49]). The data revealed that one quarter of the patients discontinued treatment, with similar discontinuation rates in drug and placebo group (24.8% versus 24.7%).…”
Section: Nocebo Effects In Antidepressant Trialsmentioning
confidence: 99%
“…The methods used for recording adverse effects changes the type and the frequency of effects reported: if a patients checks off a standardized list of symptoms, he specifies more adverse events with respect to reporting them spontaneously (Rief et al, 2009). …”
Section: Clinical Researchmentioning
confidence: 99%